Spatial Evolution of Grassland Ecological Carrying Capacity and Low-Carbon Development Pathways for Animal Husbandry in Inner Mongolia - Bingxuan Liu; Dacheng Wang; Guozhu Mao; Aixia Yang; Yue Jiao; Kaichen Zhang (Land)
Inner Mongolia’s grasslands, covering 22% of China’s total grassland area, face critical challenges in balancing livestock production with carbon sequestration under climate change pressures. This study establishes an integrated assessment framework combining remote sensing monitoring, InVEST modeling, and life cycle assessment to analyze the spatial–temporal evolution of grassland ecological carrying capacity and livestock-related carbon emissions from 2000 to 2020. Key findings reveal a 78.8% increase in actual livestock carrying capacity (from 53.09 to 94.94 million sheep units), with Tongliao experiencing 185% growth, while Alxa League showed a 229,500 sheep unit decrease. The theoretical carrying capacity grew by 50.6%, yet severe ecological pressure emerged in western regions, as evidenced by Alxa League’s grass–livestock balance index exceeding 2100%. Carbon sequestration exhibited a northeast–southwest spatial pattern, decreasing by 7.4% during 2015–2020, while greenhouse gas emissions from intensive livestock systems reached 6.40 million tons CO2-eq in Tongliao by 2020. The results demonstrate that regions combining high-intensity husbandry with low carbon storage require urgent intervention. We propose three pathways: adaptive grazing management to reduce overloading in western pastoral zones, carbon monitoring systems to enhance sequestration in vulnerable ecosystems, and emission reduction technologies for intensive farming systems. These strategies provide actionable solutions for reconciling grassland sustainability with China’s dual carbon goals, offering insights for global pastoral ecosystem management.